AB0107 The Expression of VIP Receptors, VPAC1 and Vpac2, is Related to Disease Activity in Patients with Early Arthritis. (10th June 2014) - Ortiz, A.M.; Piris, L.; González-Άlvaro, I.; Seoane, I.V.; Lamana, A.; Juarranz, Y.; Leceta, J.; Gomariz, R.P.; Martinez, C.
Abstract : Background: The vasoactive intestinal peptide (VIP) and its two receptors (VPAC1 and VPAC2) mediate critical cellular functions in the regulation of innate and adaptive immune response as has been confirmed in animal models and in vitro. These receptors are expressed on lymphocytes, macrophages and synoviocytes. The latter show a differential expression being VPAC1 the dominant receptor in osteoarthritis and VPAC2 in rheumatoid arthritis (RA). We recently reported that serum levels of VIP can be a prognostic marker in patients with RA 1 . Objectives: To describe the evolution of the expression of VPAC1 and VPAC2 in peripheral blood leukocytes from patients with early arthritis (EA) and its value as a marker of disease activity. Methods: We studied 113 patients from the PEARL registry (Princesa Early Arthritis Registry Longitudinal study) and 22 healthy donors. Follow up includes five visits (0, 6, 12, 24 and 60 months) in which we collect, per protocol, sociodemographic, clinical, laboratory and therapeutic information, as well as biological samples. 88% were female, median age at disease onset 53 [46-68] ([p25 - p75]) years and disease duration at entry 4.3 [2.6-8.2] months. 49% of patients met 1987 ACR classification criteria for RA after two years of follow up. The mRNA's expression levels of VPAC1, VPAC2, IL-6 and beta-actin (housekeeping) were determined by real-time PCR in 192 samples of peripheral blood mononuclear cells (170 from patients and 22 from controls). ANOVA with Bonferroni correction were applied for the descriptive study of the expression of VPAC1 and 2. A longitudinal multivariate analysis nested per patient visit with a GEE model was fitted to determine the effect of different independent variables on the expression of VPAC1 and 2. GLM models were applied to study the relationship between the expression of receptors and IL-6 (Stata 12 for Windows, StataCorp LP, College Station, TX, USA). Results: VPAC1 expression increased along the follow up whereas VPAC2 progressively decreased. As a result of this, a progressive increase of the VPAC1/VPAC2 ratio was observed reaching statistical significance compared to baseline at the two last visits of the follow-up (median [p25-p75]: 3.13 [1.16-5.76]; 3.74 [1.30-8.19]; 5.10 [1.63-8.72]; 7.72 [1.53-24.30]; 16.48 [2.82-39.88]; p=0.0087 y 0.0014 for the visits at 24 and 60 months). Multivariate analysis demonstrated an inverse and statistically significant relationship between the VPAC1/VPAC2 ratio and the disease activity measured by DAS28 (coefficient: -0.20, p=0.05) and a direct and close to statistical significance correlation with the treatment with disease modifying anti rheumatic drugs (coefficient: 0.78, p=0.059). In addition, we observed that VPAC1 expression was inversely related to that of IL-6, whereas VPAC2 expression showed a direct correlation (rho: -0.5, p<0.001 and rho: 0.6, p<0.001 respectively). Conclusions: The pattern of expression of VIP receptors, VPAC1 and VPAC2, shows variation over the course of patients with EA and is related to the degree of disease activity, as assessed by DAS28, and the expression of IL-6. References: Martínez C, Ortiz A M, Juarranz Y, et al. PloS one 2014; 9: e85248. Acknowledgements: This word has been funded by RETICS program, RD 12/0009 (RIER), PI11/195, PI11/505, PI12/758 from Instituto de Salud Carlos III, S2010/BMD-2350 from Comunidad de Madrid and a grant from Fundaciόn Española de Reumatología (2011). Disclosure of Interest: A. M. Ortiz Grant/research support: Instituto de Salud Carlos III and Fundaciόn Española de Reumatología, L. Piris: None declared, I. González-Άlvaro Grant/research support: Instituto de Salud Carlos III, I. Seoane Grant/research support: Instituto de Salud Carlos III and Comunidad de Madrid, A. Lamana Grant/research support: Instituto de Salud Carlos III, Y. Juarranz Grant/research support: Instituto de Salud Carlos III and Comunidad de Madrid, J. Leceta Grant/research support: Instituto de Salud Carlos III and Comunidad de Madrid, R. Gomariz Grant/research support: Instituto de Salud Carlos III and Comunidad de Madrid, C. Martinez Grant/research support: Instituto de Salud Carlos III and Comunidad de Madrid DOI: 10.1136/annrheumdis-2014-eular.3472